STAKEHOLDER COLLABORATION IN THE DEVELOPMENT OF LOCAL HERITAGE IN LAMONGAN REGENCY - Eni Febrianti; Deby Febriyan Eprilianto (Natapraja, 2022)
Local culture is a heritage nation that must be conserved even as it develops. Regency Lamongan is one place with a lot of relic culture. There is inherited culture in the form of tradition and relics very past highly crucial to maintain as well as develop Existence Thing the so research this goal for learning draft collaboration between stakeholders in developing local heritage Regency Lamongan This topic will be investigated using the descriptive qualitative technique with primary and secondary data collecting. The results of this study are known as the draft collaboration of one stakeholder with other stakeholders in developing local heritage in the district of Lamongan. Existence research is projected to have a substantial impact on the growth of local heritage in the middle modernization era.